Success factors for small rural entrepreneurs under the one-district-one-industry programme in Malaysia - Abdul Kader, R.; Mohamad, M.R.; Che Ibrahim, A.A. (2007)
This paper presents the determinants of small business as perceived and experienced by rural entrepreneurs. A sample of small rural entrepreneurs under the One-District-One-Industry (ODOI) programme in Malaysia was surveyed using a structured questionnaire. Despite the importance of both internal and external factors, this paper found that the external factors are more dominant than the internal ones in contributing to the business success of the ODOI entrepreneurs. All the external factors extracted by factor analysis narrow down to the important role of the government in promoting small business success. Therefore, the government should continuously provide assistance and favourable environment conducive to small entrepreneurship in the rural area.